Mechanically sensitive Aδ nociceptors that innervate bone marrow respond to changes in intra‐osseous pressure. (4th May 2017) - Nencini, Sara; Ivanusic, Jason
Abstract : Key points: Sensory neurons that innervate the bone marrow provide the CNS with information about pain associated with bone disease and pathology, but little is known of their function. Here we use a novel in vivo bone–nerve electrophysiological preparation to study how they respond to noxious mechanical stimulation delivered by increasing intra‐osseous pressure. We provide evidence that sensory neurons that innervate the bone marrow respond to high threshold noxious mechanical stimulation, have response properties consistent with a role in nociception, provide information about different features of an intra‐osseous pressure stimulus and express the Piezo2 mechano‐transducer molecule. Our findings show how some bone marrow nociceptors signal pain in bony diseases and pathologies that involve a mechanical disturbance or increased intra‐osseous pressure, and that the Piezo2 mechano‐transducer may be involved. Abstract: Whilst the sensory neurons and nerve terminals that innervate bone marrow have a morphology and molecular phenotype consistent with a role in nociception, little is known about their physiology or the mechanisms that generate and maintain bone pain. In the present study, we provide evidence that Aδ nociceptors that innervate the bone marrow respond to high threshold noxious mechanical stimulation, exhibit fatigue in response to prior stimulation and in some cases can be sensitized by capsaicin. They can be classified on the basis of their response properties as either phasic–tonic units that appear to code for different intensities of intra‐osseous pressure, or phasic units that code for the rate of change in intra‐osseous pressure. Three different subclasses of mechanically sensitive Aδ units were observed: phasic units that were sensitized by capsaicin, phasic units that were not sensitized by capsaicin and phasic–tonic units (that were not sensitized by capsaicin). These could also, in part, be distinguished by differences in their thresholds for activation, mean discharge frequency, latency to peak activation and peak‐to‐peak action potential amplitude. The majority of small‐diameter myelinated sensory neurons projecting to the bone marrow expressed Piezo2. Our findings indicate that Aδ mechano‐nociceptors are likely to play an important role in generating and maintaining pain in response to bony pathologies that involve a mechanical disturbance or increased intra‐osseous pressure, and imply that Piezo2 signalling may be involved in mechano‐transduction in these receptors. Key points: Sensory neurons that innervate the bone marrow provide the CNS with information about pain associated with bone disease and pathology, but little is known of their function. Here we use a novel in vivo bone–nerve electrophysiological preparation to study how they respond to noxious mechanical stimulation delivered by increasing intra‐osseous pressure. We provide evidence that sensory neurons that innervate the bone marrow respond to high threshold noxious mechanical stimulation, have response properties consistent with a role in nociception, provide information about different features of an intra‐osseous pressure stimulus and express the Piezo2 mechano‐transducer molecule. Our findings show how some bone marrow nociceptors signal pain in bony diseases and pathologies that involve a mechanical disturbance or increased intra‐osseous pressure, and that the Piezo2 mechano‐transducer may be involved.